Where the Brain Grows Old: Decline in Anterior Cingulate and Medial Prefrontal Function with Normal Aging - Pardo, José V. (2007)
Even healthy adults worry about declines in mental efficiency with aging. Subjective changes in mental flexibility, self-regulation, processing speed, and memory are often cited. We show here that focal decreases in brain activity occur with normal aging as measured with fluorodeoxyglucose and positron emission tomography. The largest declines localize to a medial network including the anterior cingulate/medial prefrontal cortex, dorsomedial thalamus, and sugenual cingulate/basal forebrain. Declining metabolism in this network correlates with declining cognitive function. The medial prefrontal metabolic changes with aging are similar in magnitude to the hypometabolism found in Mild Cognitive Impairment or Alzheimer's disease. These results converge with data from healthy elderly indicating dysfunction in the anterior attention system. The interaction of attention in the anterior cingulate cortex with memory in the medial temporal lobe may explain the global impairment that defines dementia. Despite the implications for an aging population, the neurophysiologic mechanisms of these metabolic decreases remain unknown.